Enterprise subject credit assessment method, device and equipment - SUN AIYU; LU YULI; WEN XIANLONG; SHI HONGYUN; WANG WENLONG (2024)
The invention relates to the technical field of credit assessment, in particular to an enterprise subject credit assessment method, device and equipment, and the method comprises the steps: dividing to-be-tested enterprises into supplier enterprises or terminal enterprises according to the types of the to-be-tested enterprises; off-line complete dispatch data, platform transaction data and external three-party data of the to-be-tested enterprise are obtained respectively; classifying the acquired data according to a preset classification rule; inputting the classified data into an evaluation model corresponding to the enterprise type to obtain an enterprise subject credit evaluation report; the evaluation model is a supplier enterprise evaluation model or a terminal enterprise evaluation model pre-constructed according to a preset classification rule. It can be understood that the technical scheme shown by the invention can be combined with the overall situation of the enterprise, historical real transaction